Reconsidering External Financing of Domestic Budget Deficits : Debunking Some Received Wisdom - Woo, David (IMF Policy Discussion Papers; Policy Discussion Paper, 2000)
The past decade has witnessed a steady increase in outstanding external sovereign debt issued by emerging market economies. This paper examines some of the 'received wisdom' regarding the benefits of external financing of domestic budget deficits and argues that it is often predicated on a narrow set of assumptions and incomplete evaluation of the underlying costs. The paper also suggests alternative sources of financing that can help capture some of the benefits associated with foreign financing without all of its costs.